Ultrasound-guided sclerotherapy of pingyangmycin for periorbital lymphatic malformations - Yixiao Li; Liang Wang; Dan Song; Bingxuan Jiao; Jing Li; Jie Zhou; Lei Guo (BMC Ophthalmology)
Abstract Background This study investigated the treatment outcomes of ultrasound-guided sclerotherapy with pingyangmycin for periorbital lymphatic malformations (LMs). Method A retrospective study of patients with periorbital LMs who underwent ultrasound-guided sclerotherapy in our department between 2017 and 2024 was conducted. Results One boy and seven girls with periorbital LMs were analyzed. Four cases had intraorbital lesions, two cases had lesions of the eyelids, and two cases had mixed lesions. Eight children underwent 13 sclerotherapy sessions, fluid was able to be withdrawn with a median amount of aspirate of 2 ml. After treatment, one of the eight children was lesion not seen on imaging, six showed strong improvement, and one showed weak improvement. None of the children experienced procedure-related adverse reactions. Conclusions Ultrasound-guided sclerotherapy is a treatment modality for periorbital LMs with good efficacy and few potential risks.